ESTIMATION OF THERMODYNAMIC ISOTHERMS FOR MN ADSORPTION IN SOME CALCAREOUS SOILS AT SULAIMANI GOVERNORATE. - & et al., Abdullah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was conducted to determine the description of Mn adsorption phenomena through adsorption isotherms in some calcareous soils at Sulaimani governorate. Soil samples were taken at 0-30 cm depth from five different agricultural locations. Duplicate 1 gm of soil samples were equilibrated at 298 and 318°K with 50 ml of 0.01M CaCl2 containing (0, 2.5, 5, 10, 20, and 40) mg Mn L-1 as (MnSO4. H2O). The concentration of Mn determined in solution by using ICP-OES. The amount of Mn adsorbed by each soil samples was calculated. The thermodynamic parameters ΔH°, ΔG°, ΔS° were determined using adsorption data and concentration of Mn in equilibrium solution at two different temperatures. The results indicated that the Freundlich equation is the best model to describe Mn adsorption in studied soils due to the result the higher (R2), with lower (RMSE) and (AIC). The results of (ΔH°) indicated that the Mn adsorption processes in the Sharazor, Qaradagh and Mawat soils were exothermic reactions. While, the Mn adsorption processes in both Bazian and Surdash locations were endothermic reactions. The (ΔS°) values of these soils were as follows: Surdash > Bazian> Sharazor > Qaradagh > Mawat. The results of (ΔG°) indicated that the reaction in all studied soil locations at temperature 298 °K is spontaneous, also the reaction stay spontaneous with increase temperature to 318°K only in both Bazian and Surdash locations.